Enhanced H2 production from steam gasification of biomass by red mud-doped Ca-Al-Ce bi-functional material. (15th April 2022) - Yan, Xianyao; Li, Yingjie; Sun, Chaoying; Zhang, Chunxiao; Yang, Liguo; Fan, Xiaoxu; Chu, Leizhe
Highlights: Red mud-doped Ca-Al-Ce material is proposed to use in steam gasification of biomass. Red mud-doped Ca-Al-Ce material improves H2 production in biomass gasification. H2 concentration using red mud-doped Ca-Al-Ce material reaches 69.1% after 10 cycles. Red mud-doped Ca-Al-Ce material enhances tar cracking during cycles. Ca2 Fe2 O5 generated from red mud and CaO improves oxygen vacancy. Abstract: The sorption-enhanced steam gasification of biomass (SESGB) using CaO-based materials is considered as a promising method for H2 production. Ca-Al-Ce material has been reported as a good bi-functional material in SESGB process. Red mud is a solid waste in aluminium industry with large yield, which is rich in Fe2 O3 . In this work, a red mud-doped Ca-Al-Ce bi-functional material was prepared by wet-mechanical mixing method for H2 production from SESGB. The CO2 capture, H2 production, and tar reduction performances during SESGB process using the red mud-doped Ca-Al-Ce bi-functional material were studied. The results show that the optimum addition amount of red mud in the bi-functional material is 5 wt%. After 20 SESGB cycles, the H2 concentration using the red mud-doped Ca-Al-Ce material achieves 65.1 vol%, which is 82.4% higher than that using Ca-Al-Ce material. Besides, with the addition of red mud in the bi-functional material, the tar, residue char yields and CO2 concentration decrease by 25.2%, 8.6% and 52.2%, respectively. Fe2 O3 in the red mud reacts with CaO to form Ca2 Fe2 O5 in the 1st cycle, and Ca2 Fe2 O5 is stable during 20 cycles, which is beneficial for the generation of oxygen vacancy. The oxidation states of Fe species in the material increase with the number of SESGB cycles, thus the catalytic effects on water gas shift reaction and tar reduction are promoted. The red mud addition is the key factor that results in high H2 production, CO2 capture and tar reduction performances, so the red mud-doped Ca-Al-Ce material appears promising for SESGB.